2020
DOI: 10.1039/d0ra01286f
|View full text |Cite
|
Sign up to set email alerts
|

Direct cyanation, hydrocyanation, dicyanation and cyanofunctionalization of alkynes

Abstract: Cyanation of alkynes was highlighted. Direct cyanation and hydrocyanation gave alkynyl cyanides and alkenyl nitriles. Dicyanation produced 1,2-dicyano adducts. Cyanofunctionalization afforded functional cyano compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 158 publications
0
7
0
Order By: Relevance
“… 2 In this regard, transition-metal-catalyzed difunctionalization of alkynes has become one of the most powerful synthetic methodologies for the effective synthesis of diverse complex polysubstituted olefins from abundant and readily available starting materials in an atom- and step-economical manner. 3 Nevertheless, this protocol required two elements of the p -block (RE–ER, E = B, S, Si, C…) as the coupling partners. In terms of green chemistry, the photo-catalyzed difunctionalization of alkynes has also attracted more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“… 2 In this regard, transition-metal-catalyzed difunctionalization of alkynes has become one of the most powerful synthetic methodologies for the effective synthesis of diverse complex polysubstituted olefins from abundant and readily available starting materials in an atom- and step-economical manner. 3 Nevertheless, this protocol required two elements of the p -block (RE–ER, E = B, S, Si, C…) as the coupling partners. In terms of green chemistry, the photo-catalyzed difunctionalization of alkynes has also attracted more attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Stoichiometric activation studies with different metals have revealed two major activation pathways (Scheme a). The first pathway involves mainly electron-rich metal(0) complexes, which insert via oxidative addition into the C­(sp 2 )–CN bond (pathway A ). , The second activation mode relies on the assistance of silicon, in which the prior formation of a silylated complex is followed by the migratory insertion of the nitrile into the M–Si bond (pathway B ). , Among metals reported to activate C­(sp 2 )–CN bonds, Ni, Rh, and Pd have been mainly applied in catalysis. ,, Notably, in cross-coupling reactions, apart from a particular cross-coupling between benzonitrile and azole derivatives, thus, necessitating to employ a nickel(0)/alkyl phosphine catalyst to be able to activate the C­(sp 2 )–CN bond via pathway A , biaryl formation from benzonitriles has been reported using a nickel catalyst with organometallic coupling partners such as aryl Grignard reagents, , arylboronic esters, and arylmanganese compounds (Scheme b) . The use of such organometallic species makes easy the reduction of nickel­(II)/alkyl phosphine precatalysts into nickel(0) active species, which can then insert into the C­(sp 2 )–CN bond according to pathway A .…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocyanation of unsaturated carbon-carbon bonds is a powerful method for the preparation of functionalized nitriles. Such reactions are commonly performed employing Ni-, Pd-, and Co-based catalysts and acetone cyanohydrin, Me 3 SiCN, or Zn(CN) 2 , the latter avoiding the direct use of harmful HCN [41][42][43]. In sharp contrast to simple alkynes, hydrocyanation of 1,3-diynes remains a neglected area of research.…”
Section: Hydrocyanation Processesmentioning
confidence: 99%